Multiple Correspondence Analysis towards the Change of Income and Sociodemographic of Citizens due to COVID-19 Pandemic in Malaysia - Ong Wen Xuan; Lim Chui Ting; Nurulain Nabilah Binti Muhammad Aris Fadzilah; Nora Binti Muda (Enthusiastic : International Journal of Applied Statistics and Data Science, 2022)
This paper intends to observe the economic impact and spending patterns of citizens when the spread of coronavirus occurred uncontrollably in Malaysia. The data used in this paper is the result of a first-round Special Survey ‘Effect of COVID-19 on Economy and Individual’ conducted by the Department of Statistics Malaysia. Based on the paired-t test, all the aspects tested are found to have significant differences before and during the pandemic. This is likely because citizens comply with the rules set during Movement Control Order. Next, the Chi-square test between the changes in citizens’ monthly income and sociodemographic factors are significantly associated. Therefore, factors state, gender, ethnicity, and age group of citizens are used in further analysis of multiple correspondence (MCA) to study the relationship between several categorical variables. Hence, citizens of age group 35–44 years old from Central region and Chinese citizens have no changes in their income before and during the pandemic. Citizens of age group 15–34 years old and Northern region have both increment or reduction income whereas men citizens received lower-income payments. Indian women and citizens from Eastern region tend to not work during the pandemic. This study can be a guide to the government in overcoming social problems.